Multi-objective optimization of process parameters in an area-forming rapid prototyping system using the Taguchi method and a grey relational analysis. (October 2017) - Chiu, Shih-Hsuan; Gan, Shun-Ying; Tseng, Yen-Chun; Chen, Kun-Ting; Chen, Cheng-Chin; Su, Chun-Hao; Pong, Sheng-Hong
The rapid prototyping technique has been developed over several decades. As the application becomes more widespread, the qualities of the parts produced by a rapid prototyping system must be considered. The area-forming rapid prototyping system is an emerging technology. This system has the advantage of a short build time but displays a weakness in the dimensional accuracy and surface roughness. To improve these weaknesses and simultaneously maintain a short build time, this study optimizes the process parameters using the grey relational Taguchi method. From the results, the best combinations of process parameters both for each quality and for multiple qualities are discovered. The optimization of process parameters is verified using the extra samples.